Compliance of preschool chair dimensions : Usklađenost dimenzija stolica za djecu predškolske dobi - Iliev, Boris (Array, 2019)
The proper growth and development of children is conditioned by many factors. One of the most overlooked prerequisite is the proper posture of the body in a seated position, which could be disrupted by the incorrectly dimensioned chairs used in kindergartens. To authenticate dimensions of preschool chairs in relation with contemporary European Standard 1729-1:2015, the research has been conducted in 14 public kindergartens in three European countries: Republic of Croatia, Republic of North Macedonia and Republic of Bulgaria. The results lead to the conclusion that a small number of chairs fulfil dimensional requirements. From the obtained data of the analysed chairs used by preschool children, certain deficiencies can be identified. The stated findings could be the basis for new suggestions and improvements of outdated furniture design with the aim to improve relevant regulations, standards and guidelines in order to present new preschool furniture quality parameters related to contemporary needs of children in kindergartens to the local authorities, furniture manufacturers and investors.